Adherence to recommended practices for perioperative anesthesia care for older adults among US anesthesiologists: results from the ASA Committee on Geriatric Anesthesia-Perioperative Brain Health Initiative ASA member survey - Deiner, Stacie (Perioper Med (Lond), 2020)
BACKGROUND: While specific practices for perioperative care of older adults have been recommended, little is known regarding adherence by US physician anesthesiologists to such practices. To address this gap in knowledge, the ASA Committee on Geriatric Anesthesia and the ASA Perioperative Brain Health Initiative undertook a survey of ASA members to characterize current practices related to perioperative care of older adults. METHODS: We administered a web-based questionnaire with items assessing the proportion of practice focused on delivery of care to older adults, adherence to recommended practices for older surgical patients, resource needs to improve care, and practice characteristics. RESULTS: Responses were collected between May 24, 2018, and June 29, 2018. A total of 25,587 ASA members were invited to participate, and 1737 answered at least one item (6.8%). 96.4% of respondents reported that they had cared for a patient aged 65 or older within the last year. 47.1% of respondents (95% confidence interval, 44.6%, 49.7%) reported using multimodal analgesia among patients aged 65 and older at least 90% of the time, and 25.5% (95% CI, 23.3%, 27.7%) provided preoperative information regarding postoperative cognitive changes at least 90% of the time. Over 80% of respondents reported that preoperative screening for frailty or dementia, postoperative screening for delirium, and preoperative geriatric consultation occurred in fewer than 10% of cases. Development of practice guidelines for geriatric anesthesia care and expansion of web-based resources were most frequently prioritized by respondents as initiatives to improve care in this domain. DISCUSSION: Most survey respondents reported providing anesthesia care to older adults, but adherence to recommended practices varied across the six items assessed. Reported rates of screening for common geriatric syndromes, such as frailty, delirium, and dementia, were low among survey respondents. Respondents identified multiple opportunities for ASA initiatives to support efforts to improve care for older surgical patients.